2019
DOI: 10.1039/c9cc04446a
|View full text |Cite
|
Sign up to set email alerts
|

Design of cost-efficient and photocatalytically active Zn-based MOFs decorated with Cu2O nanoparticles for CO2methanation

Abstract: Here we show for the first time a MOF that is photocatalytically active for light-assisted CO2methanation under mild conditions (215 °C), which can be further improved with the inclusion of metallic nanoparticles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Besides Ni, other transition-metal catalysts are also widely explored for photopromoted CO 2 hydrogenation for methane production . Maria et al developed a MOF with the formula of [Zn 3 (btca) 2 (OH) 2 ] (denoted as MOF­(Zn)-1) which showed photocatalytic activity for CO 2 methanation without the incorporation of metallic nanoparticles . Compared with MOF-74­(Zn), MOF­(Zn)-1 had similar valence band energies but higher conduction bands (0.06 eV), allowing electrons in it have enough energy to promote the photochemical reduction of CO 2 (−0.24 eV).…”
Section: Catalyst Development For Photopromoted Carbon Dioxide Methan...mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides Ni, other transition-metal catalysts are also widely explored for photopromoted CO 2 hydrogenation for methane production . Maria et al developed a MOF with the formula of [Zn 3 (btca) 2 (OH) 2 ] (denoted as MOF­(Zn)-1) which showed photocatalytic activity for CO 2 methanation without the incorporation of metallic nanoparticles . Compared with MOF-74­(Zn), MOF­(Zn)-1 had similar valence band energies but higher conduction bands (0.06 eV), allowing electrons in it have enough energy to promote the photochemical reduction of CO 2 (−0.24 eV).…”
Section: Catalyst Development For Photopromoted Carbon Dioxide Methan...mentioning
confidence: 99%
“…The quantum size effect gradually appears with the decrease of particles from a three-dimensional material to a two-dimensional material, a one-dimensional material, and even zero-dimensional quantum dots. In addition to the traditional semiconductor and metal-supported catalysts, polymetallic composites, carbide composites, ,,,, LDH, ,, perovskites, , MOFs, ,,,, and other materials are also showing new advantages in the photopromoted catalysis field. The research direction on catalyst preparation is developing toward fine structures to enhance the utilization of sunlight and the selectivity of methane.…”
Section: Catalyst Development For Photopromoted Carbon Dioxide Methan...mentioning
confidence: 99%
“…For example, in 2019, Cabrero‐Antonino et al . [ 148 ] designed a Zn‐based MOF composite catalyst for CO 2 methanation (Figure 19), Cu 2 O@MOF(Zn)‐1, by incorporating Cu 2 O nanoparticles into MOF(Zn)‐1 ([Zn 3 (btca) 2 (OH) 2 ], H 2 btca = 1,2,3‐benzotriazole‐5‐ carboxylic acid). The results showed that the incorporation of small Cu 2 O nanoparticles significantly promotes the catalytic activity of the resulting hybrid MOF with a TOF value of 50 × 10 –3 s –1 at 215 °C, which is much higher than the reported for Ni@MIL‐ 101(Cr) (1.63 × 10 –3 s –1 at 300 °C).…”
Section: Conversion Of Co2 To Small‐molecule Compoundsmentioning
confidence: 99%
“…In recent years, a lot of efforts have been devoted to photochemical CO 2 reduction and a great number of photocatalysts have been developed, including metal oxides and sulfides, 9,10 g-C 3 N 4 -based photocatalysts, 11–13 metal–organic frameworks (MOFs), 14–18 and covalent organic frameworks (COFs); 19,20 high CO 2 photoreduction activity in a pure CO 2 atmosphere has been achieved. In contrast, for low-concentration CO 2 reduction, there are only a few reports using N 2 /Ar to dilute high-purity CO 2 .…”
Section: Introductionmentioning
confidence: 99%